Peningkatan Kapasitas Kewirausahaan Santri Pondok Pesantren Tebuireng Jombang melalui Pelatihan Business Model Canvas - Choirunnisa, Zuyyina; Tiurma Yasinta (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This community service program is designed to strengthen the entrepreneurship capacity of Pondok Pesantren Tebuireng Jombang students through Business Model Canvas training. The method used includes a series of intensive training, starting from concept exposure, case study analysis, group discussions, to direct practice in preparing business models. The program includes mentoring and monitoring of the implementation of the business model developed by the students. This program aims to equip students with knowledge and practical skills in designing, developing, and evaluating innovative and sustainable business models. Through this training, santri are expected to develop their entrepreneurial potential, increase competitiveness, and make a positive contribution to the surrounding environment. The expected results of this program are an increase in understanding and entrepreneurial skills among santri, as well as the formation of new innovative and sustainable business models that can provide economic and social benefits to the surrounding community.